2020
DOI: 10.1515/nanoph-2020-0106
|View full text |Cite
|
Sign up to set email alerts
|

Wide gamut, angle-insensitive structural colors based on deep-subwavelength bilayer media

Abstract: AbstractWide gamut and angle-insensitive structural colors are highly desirable for many applications. Herein, a new type of lithography-free, planar bilayer nanostructures for generating structural colors is presented, which is basically composed of a deep-subwavelength, highly absorbing dielectric layer on an opaque metallic substrate. Experimental results show that a galaxy of brilliant structural colors can be generated by our structures, and which can cover ∼50% of the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Geometrical studies about d and P have been conducted to investigate the reflectance spectrum. Although the results have a narrower viewing angle (Supplementary Note 4) than other structural color devices [44,45], the performance which is displayed with the CIE and HSV color diagrams shows these color filter designs significantly reduce residual colors when turned-off. As a validation of the completely switchable encryption, practical applications of QR code encryption, two-color image switching, and overlapped images resolving are demonstrated.…”
Section: Discussionmentioning
confidence: 88%
“…Geometrical studies about d and P have been conducted to investigate the reflectance spectrum. Although the results have a narrower viewing angle (Supplementary Note 4) than other structural color devices [44,45], the performance which is displayed with the CIE and HSV color diagrams shows these color filter designs significantly reduce residual colors when turned-off. As a validation of the completely switchable encryption, practical applications of QR code encryption, two-color image switching, and overlapped images resolving are demonstrated.…”
Section: Discussionmentioning
confidence: 88%
“…Fixing the diffraction order and detecting angle, λ of the band linearly increases with d, and the k 1 is determined to be 1.71. To directly illustrate the rich colors achieved from our structures, each spectrum is converted into the RGB color value [1][2][3][19][20][21][22][23] . The Commission on Illumination (CIE) 1931 chromaticity coordinates corresponding to the generated colors with diverse grating periods are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Structural colors have attracted conspicuous interest due to their fascinating potential in the applications of sensors, optical data storage, information encryption, and display devices. Now, vivid structural colors can be generated through the interaction of light with periodic structures-most of their period (d) is comparable to the light wavelength [1][2][3] . Although as frequently suggested that the structural colored materials show superior stability compared with the colored chemical dyes and pigments, their stability at high temperature (e.g., > 700°C) is intrinsically poor due to the large surface area of the sub-micrometer structures.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism for the creation of various colors can be explained in terms of multiple light reflections that occur at the film surface (here NiO) and the interface between the film and the non-perfect metallic substrate (here Ta) as sketched in figure 3(a) [15,45]. Complex refractive indices of the film and metallic substrate results in non trivial interface phase shifts , which can be modified by varying the degree of loss in the film and substrate [13,15,16,46,47].…”
Section: Simulation Of the Reflectance Spectramentioning
confidence: 99%